Biofabricated zinc oxide nanoparticles as an eco-friendly alternative for growth promotion and management of downy mildew of pearl millet. (July 2019) - Nandhini, M.; Rajini, S.B.; Udayashankar, A.C.; Niranjana, S.R.; Lund, Ole S.; Shetty, H.S.; Prakash, H.S.
Abstract: Downy mildew caused by Sclerospora graminicola is the most devastating disease in pearl millet which leads to decrease in fodder and grain yield. Application of nanoparticles has become a major thrust for disease management in agriculture. In this study, green synthesized zinc oxide nanoparticles were evaluated for their efficiency to suppress downy mildew. Saponin rich fraction from aqueous extract of Eclipta alba was used to synthesise zinc oxide nanoparticles. The synthesized nanoparticles were characterized using UV spectroscopy, FTIR, SEM, XRD, DLS and EDAX analysis. Under laboratory and greenhouse conditions, seed treatment with synthesized nanoparticles (NP) significantly enhanced pearl millet seed germination, vigor, plant height, fresh and dry weight of seedlings. In inductively coupled plasma mass spectrometry analysis, the zinc content in nanoparticle treated seedlings was found to be higher compared to control seedlings. Sporangicidal assay of ZnO NP showed that 50 ppm of nanoparticle treatment led to plasmolysis and inhibition of spore germination of S. graminicola zoospore. ZnO NP was applied as seed treatment and foliar spray which resulted in 35% reduction in downy mildew incidence in comparison to untreated control. ZnO NP treated seedlings showed high lignification and callose deposition upon downy mildew infection. Analysis of defense enzymes showed that nanoparticle treatment significantly enhanced the activities of peroxidase, phenylalanine ammonia-lyase, lipoxygenase and polyphenol oxidase in comparison to untreated control. Semi-quantitative RT-PCR analysis revealed differentially expressed transcripts of the defense enzymes where the genes were over expressed in treated seedlings compared to low expression in control. These results indicate that synthesized ZnO NP could promote growth and induce systemic resistance in pearl millet against S. graminicola and can be effectively used to manage downy mildew. Highlights: Green synthesis of zinc oxide nanoparticles using saponin fraction of Eclipta alba . Characterization of nanoparticles was carried out using FTIR, SEM, XRD, DLS and EDAX. Seed treatment of pearl millet with zinc oxide nanoparticles improved the germination percentage and seedling vigour. Nanoparticle treatment led to plasmolysis and inhibition of spore germination of S. graminicola zoospore. ZnO NP treatment resulted in reduction in downy mildew incidence in pearl millet and the defense enzymes were found significantly over expressed in nanoparticle treated seedlings compared to untreated control.